Bank Lending in the Knowledge Economy - Dell'Ariccia, Giovanni (IMF Working Papers; Working Paper ;, 2017)
We study bank portfolio allocations during the transition of the real sector to a knowledge economy in which firms use less tangible capital and invest more in intangible assets. We show that, as firms shift toward intangible assets that have lower collateral values, banks reallocate their portfolios away from commercial loans toward other assets, primarily residential real estate loans and liquid assets. This effect is more pronounced for large and less well capitalized banks and is robust to controlling for real estate loan demand. Our results suggest that increased firm investment in intangible assets can explain up to 20% of bank portfolio reallocation from commercial to residential lending over the last four decades.